Implementasi Kebijakan Preventif Polresta Gorontalo Kota Terhadap Tindak Pidana Penganiayaan Anak Oleh Ibu Tiri - Ibrahim, Erni R.; Ekawaty Ismail, Dian; Apripari, Apripari (PT. Meja Ilmiah Publikasi, 2025)
This study aims to analyze the implementation of preventive policies by the Gorontalo City Police in handling cases of child abuse by stepmothers, as well as to identify factors that hinder and opportunities for strengthening these policies in the future. The background of this study is based on the increasing number of cases of violence against children in the family environment, particularly by stepmothers, which have serious physical and psychological impacts on the victims. This phenomenon requires a strategic response from law enforcement agencies and all elements of society to create an effective child protection system. The method used is empirical legal research with a sociological-legal approach. Primary data was obtained through in-depth interviews with perpetrators, victims, and investigators from the Women and Children Protection Unit (UPPA) of the Gorontalo City Police Department, while secondary data was collected through literature review and documentation. Analysis was conducted using a descriptive qualitative approach to organize and interpret field data based on applicable legal theories and principles. The research findings indicate that the Gorontalo City Police Department has implemented various preventive strategies, such as legal awareness campaigns and education, restorative approaches, the establishment of reporting centers and hotlines for child abuse, collaboration with non-governmental organizations, and the optimization of the Community Guidance Unit (BINMAS). These efforts have proven to increase public awareness and strengthen the child protection system, although they still face challenges such as limited resources, low public participation, and uneven legal education. This study has yielded positive outcomes, including a community-based child abuse prevention model and multi-sectoral collaboration that can be adopted in other regions. Recommendations for further research include a more in-depth study of power dynamics within stepfamilies, the effectiveness of community interventions, and the optimization of digital technology in reporting and supporting victims of child abuse.